The economic cost of sea level rise on Singapore - Dong, Wenzhen (2011)
Substantial sea level rise caused by global warming has become a major concern to policy makers in Singapore. This report focuses on the direct economic costs caused by sea level rise to Singapore. We modified the sea-level rise cost function originally proposed by Frankhauser and apply it to a set of local data. The model compares protection cost to potential direct economic loss in order to determine an optimal protection policy that minimizes the overall cost to the country. The study reaches a final result saying that a close to full protection to the Singapore's coastline is always desired due to the country’s high economic output and limited land resources. Under the optimal protection decision, the annual cost of protection will be approximately SGD 3.6 million. We concluded that the present value of the sea level rise cost over the next century varies between SGD 81.7 million and SGD 123.1 million to Singapore for different sea level rise scenario.